Risk Management of New DMTs - Rizzo, Toni (MD Conference Express, 2012)
DMTs for multiple sclerosis (MS) carry potentially serious risks, including opportunistic infections, altered response to vaccinations, development of cancer, and the appearance of autoimmune disorders. This article reviews safety data from clinical studies and post-marketing surveillance of DMTs for MS, as well as discusses the risks associated with such new therapies.